Examples:
 Expand, (2x + y + 3z)^{2}.
Given that, (2x + y + 3z)^{2}, this is in the form of (a + b + c)^{2} = a^{2} + b^{2} +
c^{2} + 2ab + 2bc + 2ca
Here a = 2x, b = y and c = 3z.
= (2x)^{2} + y^{2} + (3z)^{2} + 2.2x.y + 2.y.3z + 2.3z.2x
= 4x^{2} + y^{2} + 9z^{2} + 4xy + 6yz + 12xz
 Expand, 27x^{3} + y^{3}.
Given that, 27x^{3} + y^{3}, We write this as (3x)^{3} + (y)^{3},
this is in the form of a^{3} + b^{3} = (a+b)(a^{2}  ab + b^{2})
Here, a = 3x and b = 2y
= (3x + 2y) ((3x)^{2}  3x.2y  (2y)^{2})
= (3x + 2y)(9x^{2}  6xy + 4y^{2})
 Expand, 8x^{3}  y^{3}.
Given that, 8x^{3}  y^{3} we can write this as (2x)^{3}  (y)^{3}.
This is in the form of a^{3}  b^{3} = (a  b)(a^{2} + ab + b^{2}),
here, a = 2x, and b = y
= (2x  y)((2x)^{2} + 2x.y + y^{2})
= (2x  y)(4x^{2} + 2xy + y^{2})
Directions: Solve the following problems. Also write at least 10 examples of your own.
